2023
DOI: 10.20937/atm.53177
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the skill of gridded satellite and reanalysis precipitation products over in East and Southern Africa

Abstract: Validation of gridded precipitation products (GPP’s) increase confidence of the users and highlights possible improvements of the algorithms to handle complex rainfall forming processes. We evaluated the skill of three gridded precipitation products (GPP’s) in estimating the gauge observations and compared the precipitation trends derived from these products across the east and southern Africa region. Taylor diagrams and Kling-Gupta Efficiency (KGE) was used to assess the accuracy. A modified Mann-Kendal test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In our findings, regions, where models demonstrate higher skill, are generally those with less complex terrain, such as the relatively homogeneous Gabon and Chad regions. Generally, models exhibit poorer skill in areas characterized by a wide range in elevation (as noted in studies by Muthoni et al (2023) and Stacey et al (2023)). To enhance model skill, it is essential to ensure that the high mountains and extensive coastlines of CA are wellrepresented in the models to capture the intricate precipitation effects.…”
Section: Geographical Featuresmentioning
confidence: 95%
“…In our findings, regions, where models demonstrate higher skill, are generally those with less complex terrain, such as the relatively homogeneous Gabon and Chad regions. Generally, models exhibit poorer skill in areas characterized by a wide range in elevation (as noted in studies by Muthoni et al (2023) and Stacey et al (2023)). To enhance model skill, it is essential to ensure that the high mountains and extensive coastlines of CA are wellrepresented in the models to capture the intricate precipitation effects.…”
Section: Geographical Featuresmentioning
confidence: 95%
“…Others have suggested that CHIRPS might overestimate rainfall in the nearby Kisumu region along the Western shores of Lake Victoria 82 . In addition, 65 suggested that CHIRPS had a slight dry bias, although in general performing well. In other regions of the world, CHIRPS has been found to struggle to capture extreme rainfall 83 .…”
Section: Methodsmentioning
confidence: 99%